2000
DOI: 10.1002/1520-6432(200009)83:9<1::aid-ecjb1>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Vibration stress and temperature dependence of piezoelectric resonators with lead-zirconate-titanate ceramics

Abstract: It has been shown that the temperature of a piezoelectric ceramic resonator increases, and its electromechanical characteristics vary, when the resonator is continuously driven at a high level of vibration stress in a resonant mode. The effects of temperature and vibration stress on specific electromechanical characteristics of typical piezoelectric ceramics were separated using two measurement methods: the continuous‐voltage‐wave drive method, which results in increased temperature, and the burst‐voltage‐wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…All coefficients of the investigated PZT material, with the exception of Poisson's ratio σ, increase with increasing v, which is in agreement with the results reported in literature for hard PZT . The comparatively large electric field or mechanical stress during vibration at high v is accounted to be responsible for the increase of these coefficients .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…All coefficients of the investigated PZT material, with the exception of Poisson's ratio σ, increase with increasing v, which is in agreement with the results reported in literature for hard PZT . The comparatively large electric field or mechanical stress during vibration at high v is accounted to be responsible for the increase of these coefficients .…”
Section: Resultssupporting
confidence: 91%
“…All coefficients of the investigated PZT material, with the exception of Poisson's ratio , increase with increasing v , which is in agreement with the results reported in literature for hard PZT. 22,38,44 The comparatively large electric field or mechanical stress during vibration at high v is accounted to be responsible for the increase of these coefficients. 45,46 Similar to the decrease of the quality factor (see previous sections), this increase is attributed to an enhanced motion of ferroelectric/ferroelastic domain walls.…”
Section: Piezoelectric Coefficients-(31) (33) and (P) Modementioning
confidence: 99%
“…Additionally, by plotting the response through resonance using a bi-directional frequency sweep, the nonlinearity in the vibration responses is clearly exhibited. Nonlinear softening has been reported to occur in piezoelectric transducers due to driving the transducer above some threshold amplitude of vibration (Umeda et al, 2000). There is evidence of nonlinear softening in both Figure 6(a) and (c), which are the vibration responses of the transducer with end-caps in the R-phase, exhibited as a decrease in frequency for increased input voltage.…”
Section: Dynamic Characterization Of the Transducermentioning
confidence: 99%
“…It was also reported that a loss factor is dependent on strength of electric field and temperature (Gerthsen et al, 1980;Takahashi et al, 1994;Beige, 1983;Mukherjee et al, 2011). It should be noted that although elastic, dielectric and piezoelectric terms are temperature dependent, they are less sensitive compared to the loss factor for the evaluation of amplitude values (Albareda et al, 2000;Umeda et al, 2000a;Umeda et al, 2000b).…”
Section: Nonlinearity Of Ultrasonic Systemsmentioning
confidence: 99%